Pendidikan Agama Islam dan Visi Indonesia Emas 2045: Studi Literatur tentang Integrasi Nilai Keislaman, Kebangsaan, dan Global Citizenship - Sonia Isna Suratin; Muzawir Munawarsyah (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
Islamic Religious Education has a strategic role in preparing a generation of the nation with religious, nationalist, and globally competitive characters in line with the Vision of Golden Indonesia 2045. The challenges of globalization, value disruption, and the increasing complexity of social life require Islamic Religious Education to not only be oriented towards strengthening spiritual aspects, but also be able to integrate Islamic values ​​with national values ​​and global citizenship in a harmonious and contextual manner. This study aims to systematically analyze the concepts, patterns, and urgency of integrating Islamic, national, and global citizenship values ​​in Islamic Religious Education as a foundation for the development of future Indonesian human resources. This study uses a qualitative approach with a literature study type. Data collection techniques are carried out through searching and reviewing written sources in the form of books, scientific journal articles, educational policy documents, and relevant research reports. Data analysis techniques use content analysis through the stages of data reduction, data presentation, and interpretative conclusion drawing. Data validity is maintained through diligent observation, referential adequacy, and triangulation of sources and theories. The research results indicate that the integration of Islamic, national, and global citizenship values ​​in Islamic Religious Education can be realized through strengthening a curriculum based on moderation values, developing reflective and contextual pedagogy, and internalizing the values ​​of tolerance, justice, and global responsibility. This research implies the importance of strengthening adaptive and transformative Islamic Religious Education policies and practices to support the realization of a Golden Indonesia 2045 generation that is faithful, moral, patriotic, and has a global perspective.